2021
DOI: 10.1002/jmv.27369
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of rapid antigen detection test for individuals at risk of SARS‐CoV‐2 under quarantine

Abstract: We read with interest the recent article by Cassuto et al. 1 about selftesting of rapid antigen detection (RAD) test from coronavirus disease 2019 (COVID-19) individuals. For the 100 participants with valid results,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…The sampling process was observed in 17 of the self-sampling studies (22 datasets), totaling 19,280 samples (60.6%) 12 , 13 , 37 41 , 43 , 46 , 48 , 49 , 51 , 52 , 54 , 58 , 61 , whereas sampling was not observed in four studies (4 datasets; 10.8%) 35 , 36 , 47 , 59 . For the remaining ten studies (10 datasets; 27.0%), it was unclear whether the sampling was observed or not 42 , 44 , 45 , 50 , 53 , 55 57 , 60 , 62 . Overall, 78.6% of the self-testing studies were carried out at a testing site, and the testing procedure was observed (without providing instructions) by the study team in three studies (1083 samples; 2.9%) 11 , 28 , 32 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sampling process was observed in 17 of the self-sampling studies (22 datasets), totaling 19,280 samples (60.6%) 12 , 13 , 37 41 , 43 , 46 , 48 , 49 , 51 , 52 , 54 , 58 , 61 , whereas sampling was not observed in four studies (4 datasets; 10.8%) 35 , 36 , 47 , 59 . For the remaining ten studies (10 datasets; 27.0%), it was unclear whether the sampling was observed or not 42 , 44 , 45 , 50 , 53 , 55 57 , 60 , 62 . Overall, 78.6% of the self-testing studies were carried out at a testing site, and the testing procedure was observed (without providing instructions) by the study team in three studies (1083 samples; 2.9%) 11 , 28 , 32 .…”
Section: Resultsmentioning
confidence: 99%
“…Two self-testing and one self-sampling studies provided additional instructional videos 24 , 29 , 45 . Regarding self-testing studies, four studies provided study-specific test instructions since no manufacturer instructions for self-testing were available at the time 11 , 24 , 25 , 29 .…”
Section: Resultsmentioning
confidence: 99%
“…Finally, due to the role of PHLSB in this study, we confirmed preliminary SARS-CoV-2 positive CNTS specimens, sensitivity and specificity of using CNTS for diagnosis of SARS-CoV-2 could not be obtained. However, we performed a small study to show the usefulness of CNTS for diagnosis of SARS-CoV-2 with the use of RT-PCR and antigen techniques [ Mak et al, 2021b ].…”
Section: Discussionmentioning
confidence: 99%
“…Across 36 datasets from 31 self-sampling studies, sensitivity again ranged widely from 20.0% [33] to 100% [35] with wide CIs. Speci city for selfsampling studies ranged from 96.4% [58] to 100% [12]…”
Section: Performance Of Self-testing and Self-sampling In Comparison ...mentioning
confidence: 99%